Lower extremity muscle pathology in myotonic dystrophy type 1 assessed by quantitative MRI - Heskamp, Linda (Neurology, 2019)
OBJECTIVE: To determine the value of quantitative MRI in providing imaging biomarkers for disease in 20 different upper and lower leg muscles of patients with myotonic dystrophy type 1 (DM1). METHODS: We acquired images covering these muscles in 33 genetically and clinically well-characterized patients with DM1 and 10 unaffected controls. MRIs were recorded with a Dixon method to determine muscle fat fraction, muscle volume, and contractile muscle volume, and a multi-echo spin-echo sequence was used to determine T2 water relaxation time (T2(water)), reflecting putative edema. RESULTS: Muscles in patients with DM1 had higher fat fractions than muscles of controls (15.6 ± 11.1% vs 3.7 ± 1.5%). In addition, patients had smaller muscle volumes (902 ± 232 vs 1,097 ± 251 cm(3)), smaller contractile muscle volumes (779 ± 247 vs 1,054 ± 246 cm(3)), and increased T2(water) (33.4 ± 1.0 vs 31.9 ± 0.6 milliseconds), indicating atrophy and edema, respectively. Lower leg muscles were affected most frequently, especially the gastrocnemius medialis and soleus. Distribution of fat content per muscle indicated gradual fat infiltration in DM1. Between-patient variation in fat fraction was explained by age (≈45%), and another ≈14% was explained by estimated progenitor CTG repeat length (r(2) = 0.485) and somatic instability (r(2) = 0.590). Fat fraction correlated with the 6-minute walk test (r = −0.553) and muscular impairment rating scale (r = 0.537) and revealed subclinical muscle involvement. CONCLUSION: This cross-sectional quantitative MRI study of 20 different lower extremity muscles in patients with DM1 revealed abnormal values for muscle fat fraction, volume, and T2(water), which therefore may serve as objective biomarkers to assess disease state of skeletal muscles in these patients. CLINICALTRIALS.GOV IDENTIFIER: NCT02118779.